Monitoramento e disseminação cooperativa de eventos emergenciais apoiado por agrupamento de veículos - Andrade Júnior, José Everaldo de (2019)
Critical urban events, for example accidents, disasters and crimes, occur at a random way and they need to be dealt with by public authorities quickly to maintain the proper operation of cities. Such authorities need accurate information of the event context to enable a quick and correct handling of the event with the least possible impact on the daily life of the population. But the main challenges for an efﬁcient handling of an event fall precisely in its random nature, and in the speed and accuracy of the notiﬁcation of its manifestation to the authority. Moreover, the fact that this notiﬁcation depends on human intervention aggravates this situation, given that, due to the circumstances of the event, information passed on by people may not match the reality and compromise the handling of the event. The omnipresence of vehicles in urban environments, and their communication, processing and monitoring capabilities, allow to employ VANETs to support the dissemination and handling of such events. Thus, this paper proposes MINUET, a system to support the monitoring and dissemination of urban events, which operates in an ad hoc vehicular network. It uses a cooperative-based strategy where vehicles are able to dynamically coordinate the monitoring and distributed dissemination of information of events in real time by the means of clusters. Results using the NS3 simulator demonstrated the effectiveness and efﬁciency of MINUET during the detection, monitoring, dissemination and delivery of real-time event information to the responsible entities under the different trafﬁc and event contexts normally present in urban areas. The performance of the clustering techniques used in MINUET was also veriﬁed.